ANALYSIS OF TRAVERSE RIBBING EFFICIENCY IN MILLING PLANER WITH TRAVELING BRIDGES - V. I. Turomsha; S. S. Dovnar; A. S. Truskovsky; Ali Tumi El-Mabruk Abujafer (Наука и техника)
A finite element modeling of recoverable traverse deformations of heavy milling planers with traveling bridges has been carried out in the paper. The paper reveals specific deformation modes – twisting, bending and cross-section crabbing. Various variants of internal traverse ribbing have been investigated in the paper. The paper shows a ribbing influence on some deformation modes and its efficiency with double walls. Recommendations on provision of base components’ rigidity with material economical expenditure is given in the paper.